Characteristics and Deposit Stratigraphy of Submarine-Erupted Silicic Ash, Havre Volcano, Kermadec Arc, New Zealand - Murch, Arran P.; White, James D. L.; Carey, Rebecca J. (Frontiers in Earth Science, 2019)
Submarine eruptions dominate volcanism on Earth, but few are observed or even identified. Knowledge of how they operate is largely based on inference from ancient deposits, lagging by a decade or more our understanding of subaerial eruptions. In 2012, the largest wholly deep-subaqueous silicic eruption with any observational record occurred 700–1220 m below sea level at Havre volcano, Kermadec Arc, New Zealand. Pre- and post-eruption shipboard bathymetry surveys, acquisition by autonomous underwater vehicle of meter-scale-resolution bathymetry, and sampling by remote-operated vehicle revealed 14 seafloor lavas and three major seafloor clastic deposits. Here we analyze one of these clastic deposits, an Ash with Lapilli (AL) unit, which drapes the Havre caldera, and interpret the fragmentation and dispersal processes that produced it. Seafloor images of the unit reveal multiple subunits, all ash-dominated. Sampling destroyed layering in all but two samples, but by combining seafloor imagery with granulometry and componentry, we were able to determine the subunits’ stratigraphy and spatial extents throughout the study area. Five subunits are distinguished; from the base these are Subunit 1, Subunit 2a, Subunit 3, Subunit 4 (comprising the coeval Subunit 4 west and Subunit 4 east), and Subunit 2b. The stratigraphic relationships of the four AL unit subunits to other seafloor products of the 2012 Havre eruption, coupled with the wealth of remote-operated vehicle observations and detailed AUV bathymetry, allow us to infer the overall order of events through the eruption. Ash formed by explosive fragmentation of a glassy vesicular magma and was dispersed by a buoyant thermal plume and dilute density currents from which Subunits 1 and 2 were deposited. Following a time break (days/weeks?), effusion of lava along the southern caldera rim led to additional ash generation; first by syn-extrusive ash venting, quenching, brecciation, and comminution (S3 and S4e) and then by gravitational collapse of a dome (S4w). Slow deposition of extremely fine ash sustained S2 deposition across the times of S3 and S4 emplacement, so that S2 ash was the last deposited. These thin ash deposits hold information critical for interpretation of the overall eruption, even though they are small in volume and bathymetrically unimpressive. Ash deposits formed during other submarine eruptions are similarly likely to offer new perspectives on associated lavas and coarse pumice beds, both modern and ancient, and on the eruptions that formed them. Submarine ash is widely dispersed prior to deposition, and tuff is likely to be the first product of eruption identified in reconnaissance exploration; it is the start of the trail to vent hydrothermal systems and associated mineralized deposits of submarine volcanoes, as well as a sensitive indicator of submarine eruptive processes.